2017
DOI: 10.1016/j.micres.2016.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Rhizospheric soil and root endogenous fungal diversity and composition in response to continuous Panax notoginseng cropping practices

Abstract: Rhizosphere and endophytic fungal communities are considered critically important for plant health and soil fertility. In response to continuous cropping, Panax notoginseng becomes vulnerable to attack by fungal pathogens. In the present study, culture-independent Illumina MiSeq was used to investigate the rhizospheric and root endophytic fungi in response to continuous Panax notoginseng cropping practices. The results demonstrated that fungal diversity is increased inside the roots and in rhizospheric. Ascomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
114
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(138 citation statements)
references
References 38 publications
23
114
1
Order By: Relevance
“…In this study, fungal diversity showed inconsistency; however, compared to CK, fresh and old cropped tea fields significantly decreased the fungal diversity ( Figure 2D,E). These results are in line with previous findings, in which the fungal diversity decreased in response to continuous planting of Panax notoginseng [40]. The decrease in fungal diversity has been recognized as a foremost threat to ecosystem services [41], resulting in partial loss of soil function (plant growth promotion or disease inhibition) [42,43], which may result in reduced tea production under a consecutive monoculture system.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, fungal diversity showed inconsistency; however, compared to CK, fresh and old cropped tea fields significantly decreased the fungal diversity ( Figure 2D,E). These results are in line with previous findings, in which the fungal diversity decreased in response to continuous planting of Panax notoginseng [40]. The decrease in fungal diversity has been recognized as a foremost threat to ecosystem services [41], resulting in partial loss of soil function (plant growth promotion or disease inhibition) [42,43], which may result in reduced tea production under a consecutive monoculture system.…”
Section: Discussionsupporting
confidence: 91%
“…Correspondingly, Xiong et al [35] also observed a significant influence on alterations in the fungal community structure during continuous cultivation of vanilla. In fact, this phenomenon also occurs in both perennials and annual crops such as soybean [10,39], Panax notoginseng [40], potato [9], and coffee [6] continuous cropping systems. In addition, the UPGMA and PCoA helped to explain that the fungal communities fluctuated after 30 years of tea monoculture.…”
Section: Discussionmentioning
confidence: 99%
“…Ascomycota, Basidiomycota, and Zygomycota were the top three fungal phyla detected in both healthy and diseased A. macrocephala plants, which was similar to the profile of soil fungi. This pattern fits with earlier publications, which have shown that endophytic fungi are primarily derived from soil fungi that enter the plants via roots, tubers, leaves and stems (Dai et al, 2010;Tan et al, 2017b). At the genus level, Fusarium and Alternaria abundance significantly increased in the root-rot diseased A. macrocephala samples.…”
Section: Discussionsupporting
confidence: 91%
“…The soil which was loosely attached to the roots was removed by gentle shaking. Tightly bound soil was considered rhizospheric and was obtained by firmly shaking the root system in a sterile plastic bag (Kobayashi et al, 2015;Tan et al, 2017b). The rhizospheric soil samples were thoroughly mixed, and randomly divided into three subsamples, as described previously (Yu et al, 2019).…”
Section: Study Site and Experimental Designmentioning
confidence: 99%
“…This implies that Proteobacteria is generally adapted to the rhizosphere environment across diverse plant species. In terms of fungi, there were the distinct dominant phyla between the growth stages, but these dominant phyla, Basidiomycota, Ascomycota, Chytridiomycota and Zygomycota, have been identified as dominant phyla in previous studies on Panax notoginseng (Tan et al, 2017), ramie , and wheat and canola (Schlatter et al, 2019). However, unlike plant and animal ecology, there is not a clear definition for the dominant phylum in microbial ecology until now.…”
Section: Discussionmentioning
confidence: 98%